Web Information Architecture: methodologies, methods, technological applications and user studies (Ágora de Heterodoxias, 2023)
The recent development of information technologies has placed society in a digital ecosystem, within which it is necessary to structure information architectures that respond to the specific and diverse needs of users. In this sense, with this scientific process, the objective was to carry out a systematic literature review regarding the information architecture on the web: methodologies, methods, technological applications and user studies. For this exercise, a methodology was established for the formulation of research questions, inclusion and exclusion of scientific papers, sources of information, search criteria, implementation of search equations, debugging of results, selection of scientific works, diagramming of relations and description of results. Subsequently, from two selected databases, the results yielded 1989 scientific papers, of which 18 selected for analysis and description, with respect to the research focus. We concluded that the background of all these projects is to deepen the improvement regarding the development of information architectures.
Keywords: Information architecture, methodologies; methods; technological applications; user studies,; web